Uncovering the hidden intangible factors of hotel employees’ turnover intention during covid phenomenon - Chaichi, Kamelia; Zawawi, Dahlia; Abdul Aziz, Yuhanis; Leong, Mei Kei (Sage Publications India Pvt. Ltd, 2024)
The extant literature on hospitality and human resource management has not yet uncovered the hidden intangible chain of employee turnover intention, particularly in the hotel context. A theoretical framework was developed by applying the tenets of the theory of planned behaviour, social cognitive theory and the multi-dimensional commitment model. More specifically, this study investigated the impact of staff core personality (core confidence traits and core self-evaluation) on employees’ positive attitudes towards the organization, ultimately decreasing employee turnover intention. Further, the study scrutinized the moderating impact of organizational commitment dimensions in the extended model and the links that were missing in prior literature. It employed a self-administered survey and obtained 300 usable responses. The data were analysed through partial least squares structural equation modelling (PLS-SEM) software. The results revealed that all the core personality factors (CSE and core confidence traits, including resilience, hope and optimism) and self-efficacy significantly affect the staff’s positive attitude. Moreover, the study established the moderating impact of affective commitment and continuous commitment on the connection between attitude and employees’ intention to leave the organization. This article recommends several practices that hotel human resource managers can utilize to reduce employee turnover intention and upsurge the sustainability of the hotel industry.